2020
DOI: 10.1016/j.jalz.2019.08.189
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Alzheimer's disease diagnosis within 14 years through Aβ misfolding in blood plasma compared to APOE4 status, and other risk factors

Abstract: Introduction:Alzheimer's disease (AD) has a long prodromal stage and identifying high-risk individuals is critical. We aimed to investigate the ability of A misfolding in blood plasma, APOE4 status, and dementia risk factors to predict diagnosis of AD.Methods: Within a community-based cohort, A misfolding in plasma measured by immuno-infrared sensor and APOE genotype were determined at baseline in 770 participants followed over 14 years. Associations between A misfolding, APOE4, and other predictors with clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
(111 reference statements)
1
22
0
Order By: Relevance
“…These two groups might not have been differentiated in the raw data, as the average follow-up time in this cohort was only 2.7 years, which might be too short. Previous studies showed that our structure biomarker predicts conversion up to 14 years in advance [35]. In the ESTHER study, the average conversion time to ADdementia was 8 years after baseline blood sample was taken [25].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These two groups might not have been differentiated in the raw data, as the average follow-up time in this cohort was only 2.7 years, which might be too short. Previous studies showed that our structure biomarker predicts conversion up to 14 years in advance [35]. In the ESTHER study, the average conversion time to ADdementia was 8 years after baseline blood sample was taken [25].…”
Section: Discussionmentioning
confidence: 82%
“…We have recently validated Aβ misfolding as a structure biomarker in plasma for probable AD (prospective Essen cohort) [24], for prodromal AD (BioFINDER) [25], and for preclinical cognitively unimpaired AD subjects (population-based ESTHER cohort) [25]. Including APOEε4 as a risk factor, early AD pathology could be identified with an AUC of 0.84 as early as 14 years before the clinical diagnosis of AD [35]. Remarkably, consistent cutoffs have been observed across all studies with a general threshold of < 1644 cm − 1 , indicating high misfolding in individuals with dementia due to AD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we identified that protein folding pathways were significantly downregulated in microglial cells with Pb treatment. Dysregulation of protein folding is hypothesized to be a major underlying etiologic factor for the development of Alzheimer's disease (Selkoe 2003;Stocker et al 2019). One of our top downregulated genes overall, and within individual clusters, was Hbb-bs.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, the presence of A pathology can be determined either by cerebrospinal fluid (CSF), positron emission tomography (PET) imaging, or recently also by blood samples. 12,13 While prescribed for the same goal, a non-negligible proportion of patients can present with discordant results between CSF and PET. 14 CSF is considered to indicate the presence of amyloid pathology in its earliest stages, but it plateaus relatively early in the AD disease course, while amyloid PET imaging shows continued build-up of amyloid burden beyond the CSF plateau 15 and it provides information on the spatial distribution of the pathology in the brain.…”
Section: Introductionmentioning
confidence: 99%